Efficacy of medical grade honey in the treatment of diabetic foot ulcers: a systematic review (Research, Society and Development, 2022)
Objective: To analyze the effectiveness of medical grade honey in the treatment of diabetic foot ulcers. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “honey”, “wound”, “wound healing”, “honey dressing” and “diabetic foot”. Full articles, available in Portuguese, English and Spanish, published between January 2010 and December 2020, research conducted in humans and studies focusing on honey in the treatment of diabetic foot ulcers were included. Results: Seven articles made up the final sample of this study, with the highest production in China (n: 03). All studies used the Randomized Clinical Trial methodology, characterizing the studies as presenting a strong level of evidence (II). The treatment of diabetic foot ulcers with honey was found to have good overall efficacy, such that four studies had higher healing rates compared to their respective control groups and shorter healing times. It was found that the results presented suggested that the honey dressing was associated with a higher rate and earlier bacterial clearance time compared to other dressings. Conclusion: It was found that medical grade honey was effective in the treatment of diabetic foot ulcers, promoting high healing rates in a shorter period and high bacterial load reduction. However, some coverages used as controls showed greater efficacy, prompting more robust studies for a greater generalization of the results.